In-depth genetic characterization of the SARS-CoV-2 pandemic in a two-year frame in North Macedonia using second and third generation sequencing technologies - Vukovikj, Maja; Boshevska, Golubinka; Janchevska, Elizabeta; Buzharova, Teodora; Preshova, Ardian; Simova, Milica; Peshnacka, Aneta; Kocinski, Dragan; Kuzmanovska, Gordana; Memeti, Shaban; Gjorgoski, Icko (Frontiers in Virology, 2023)
The widespread severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continuously impacts the worldwide economy and public health. Molecular characterization of full-length SARS-CoV-2 genomes is necessary to understand the origin, transmission pathways and to identify the mutations that affect the transmissibility and pathogenicity of the virus. The aims of our study were to give an in-depth virologic and epidemiological overview of the SARS-CoV-2 pandemics in a two-year frame in North Macedonia, to assess the frequency and distribution of the circulating SARS-CoV-2 variants, to discern the molecular evolution of SARS-CoV-2 through genetic characterization and phylogenetic analysis and to discover, if any, connection between specific SARS-CoV-2 haplotypes and the severity of the clinical symptoms. Our results showed that out of 284.549 tested respiratory samples for SARS-CoV-2, 21.51% were positive. The highest incidence of SARS-CoV-2 positive cases among men was observed in the 60+ group (4.170,4/100.000) and a statistically significant difference between men and women was noticed in the same age group (0.0001). Additionally, the mortality among men was 1.8 times higher compared to women in the 60+ group and consequently the number of death cases among men in the same group was significantly higher compared to the women (p=0.001). A total of 327 samples were sequenced in the period March 2020 - August 2021, showing the temporal distribution of SARS-CoV-2 variants circulating in North Macedonia. The phylogenetic analysis showed that most of the viral genomes were closely related and clustered in four distinctive lineages, B.1, B.1.1.7, B.1.351 and B.1.617.2. A statistically significant difference was observed in the 2C_1 haplotype (p=0.0013), where 10.5% of the patients were hospitalized due to severe clinical condition. Sequencing has played an invaluable role in the response to the COVID-19 pandemic and it was used to complement outbreak investigations, to study viral transmission, to identify emerging variants, and to understand vaccine breakthrough infection. The present work is the first molecular study giving a comprehensive overview of the genetic landscape of circulating SARS-CoV-2 viruses in North Macedonia in a period of two years.